1989
DOI: 10.1530/jrf.0.0860589
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of plasma progesterone concentrations to ovarian H-type lipase activity during pseudopregnancy in the rat

Abstract: Conditions for extraction and assay of hepatic type (H-type) lipase from rat ovaries were studied. An alkaline buffer with protease inhibitors and detergents gave the most efficient extraction. The specificity of the assays was ascertained using antiserum to H-type lipase from heparin perfusates of rat livers. H-type lipase activity was determined in ovarian compartments during pseudopregnancy (1-13 days) as well as during the ensuing period of luteal regression (Day 17). The activity was low in the luteal com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

1991
1991
2007
2007

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…Ovaries and adrenals of rats and humans have been shown to contain a lipase activity (liver-or l-type lipase) similar to hepatic lipase (HL) normally present in liver sinusoids [1][2][3][4][5]. Whereas the liver enzyme plays a role in the uptake of circulating lipoproteins and its components, the l-type lipase in the steroidogenic organs is suggested to mediate the delivery of high-density lipoprotein cholesterol required for hormone synthesis [6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ovaries and adrenals of rats and humans have been shown to contain a lipase activity (liver-or l-type lipase) similar to hepatic lipase (HL) normally present in liver sinusoids [1][2][3][4][5]. Whereas the liver enzyme plays a role in the uptake of circulating lipoproteins and its components, the l-type lipase in the steroidogenic organs is suggested to mediate the delivery of high-density lipoprotein cholesterol required for hormone synthesis [6].…”
Section: Introductionmentioning
confidence: 99%
“…The l-type lipase activity in the ovaries varies during the oestrous cycle and lactation in parallel with progesterone and 20h-hydroxyprogesterone output [2,7,8].…”
Section: Introductionmentioning
confidence: 99%
“…These assays demonstrated that the human HL promoter region is active in these cells, and that promoter activity in these cells is enhanced by 8-Br-cAMP, which mimics the effect of ACTH. An increased HL expression in these organs may be important to maintain the high steroid production, possibly by accelerating the SR-BI mediated uptake of HDL cholesterol (6,14,16,17). The presence of full-length HL mRNA in these activated adrenals strongly suggests that at least part of the adrenal HL activity originates from local synthesis.…”
Section: Discussionmentioning
confidence: 99%
“…3.1.1.34) activity is present in the adrenal cortex of several mammals including man (1)(2)(3)(4), as well as in rat ovaries (5)(6)(7)(8). The HL activity from rat, mouse, and human adrenals is indistinguishable from HL in liver and post-heparin plasma (2,5,(8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation